Az orosz embargó hatása az Európai Unió gazdaságára - Tóth Zsófia (2016)
In this paper, I focus on the economic sanctions which have taken place over the past few years. In the world economy sanctions, such as embargoes play a significant role. I chose this topic because over the years many such events have taken place that have affected the whole world. I definitely focus on current events, so I studied the eco-nomic impact of the Russian import embargo. In the first part of my thesis, I tried to give an overall description of trade re-strictions. I presented the historical development of these restrictions. Then, I also listed the types and general characteristics of the trade restrictions. I presented the basic defini-tions related to trade limitations. After that I gave a representative picture of an import embargo. I showed the sample of the relationship between the United States and Iran. I al-so listed the impact of the American embargo on the economy of Iran. In the second part of my paper, I introduced the development of the relationship between the European Un-ion and Russia. I tried to give a general overview about this connection, how it began and developed. Then, I presented the trade relations between the two parties. I listed the most important goods, which are traded. After that, I analysed the impact of both sanctions - the sanction imposed by the EU and sanction imposed by Russia – on the affected econo-mies and economic sectors. I also analysed how the decreased agri-food export to Russia can influence the GDP of the EU and the chosen Member States. In the third part of the thesis, I gave some details about how the EU would like to solve this situation. I introduced the economic impact of the embargo using statistical datas. I found the needed material on the website of the EUROSTAT, the Worldbank and the WTO. The lit-erature concentrate on the EU-Russia relations, since Russia has an international influence, and has a special relationship with EU. I got information from the publications and formal summaries of the EU. I also searched for information about the actual events and process on the Internet.